Association Between Self-Rated Political Orientation and Attitude Toward the Cash Transfer Policy During the COVID-19 Pandemic: A Nationwide Cross-Sectional Survey Conducted in South Korea - Kim, Jin-Hwan; Jang, Deok Hyun; Jang, Won Mo (Frontiers in Public Health, 2022)
Objective This study assessed the relationship between self-rated political orientation and attitude toward the cash transfer policy during the COVID-19 pandemic. Methods This cross-sectional study conducted in South Korea during the pandemic included a stratified sample of 1,004 respondents (aged 19 years and older). We tested the hypotheses that political orientation shapes attitudes toward social policies and that other socioeconomic factors might have relatively minor importance. Logistic regression was used to identify associations between political orientation and attitude toward the cash transfer policy. Average marginal effects were calculated to determine the effect size of each variable. Results Political orientation, age, and residential area were correlated with attitudes toward the policy. Compared to the conservatives, the non-committed and the moderate showed about 10% more favorable attitudes, and the progressive group showed robust support. People in their 30s and 40s showed similar attitudes to the 18-29 group, while older people showed much lower support. Compared to the Seoul metropolitan area, residents of the Ho-nam area showed favorable attitudes, and those of the Yeong-nam area had relatively unfavorable attitudes. Conclusions This study suggests that attitudes toward the cash transfer policy are mainly affected by political orientation. Although these results illuminate pandemics' social and political dimensions, further efforts are needed to fully understand the determinants and mechanisms of attitudes toward policies outside the traditional health policy scope.